Enhanced dynamic exergy analysis of a micro-jet (?-jet) engine at various modes - Balli, Ozgur; Aygun, Hakan; Turan, Onder (Pergamon-Elsevier Science Ltd, 2022)
In the current study, advanced exergo-dynamic analysis of a micro-turbo jet (mu-jet) along with conventional exergy analysis is presented in various running shaft speed modes. In this context, major advanced exergetic indicators of mu-jet components are evaluated at the various running testing. The operation modes were represented as operation shaft speeds between 48,850 and 77,000 RPM (revolution per minute), while mu-jet produced within the range of 45.01-121.27 N thrust force in these modes. Improvement potentials of turbomachinery components and exergy destruction rates are calculated throughout the real-time testing modes. According to the analysis, the combustor has the lowest exergy efficiency ranging from 41.06% to 50.18%. Also, the study shows that the exergy efficiency values of the experimental mu-jet are found to be as 6.56% at Mode-1, 10.12% at Mode-2, 15.46% at Mode-3 and 17.02% at Mode-4, respectively. Other important findings for mu-jet are that unavoidable exergy destruction rate varies between 94.89% and 95.79%, while endogenous exergy destruction value changes between 89.79% and 91.47% in these modes. Thanks to the present analysis, the methods decreasing avoidable exergy destruction that changes between 4.21% and 5.11% could be focused. (C) 2021 Elsevier Ltd. All rights reserved.
Keywords: Advance exergy; Microjet; Turbojet; Propulsion